2017
DOI: 10.1080/17518253.2017.1395081
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of silver nanoparticles using Peganum harmala extract as a green route

Abstract: In this study, we investigated the synthesis of silver nanoparticles using Peganum harmala water extract at ambient temperature. The Ag nanoparticles (AgNPs) were characterized by ultravioletvisible spectroscopy (UV-vis), Fourier transform infrared spectroscopy (FT-IR), powder X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), and transmission electron microscopy (TEM). The average particle size of the silver nanoparticles was about 23 nm. Inhibitory activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 49 publications
3
31
0
Order By: Relevance
“…Moreover, the antibacterial effects of the FI-AgNPs are owing to the interaction of AgNPs with the three-dimensional microbial structure of the cell walls of bacteria. The destruction of the bacterial cell wall may also be attributed to the release of ROS (reactive oxygen species) that can damage membrane protein and nucleic acid [52,53]. Bagherzadeh et al [54] compared the antibacterial effects of biosynthesized AgNPs prepared using saffron extract and market purchased AgNPs and showed that the extract of the saffron plant and purchased AgNPs did not show enough antibacterial effects but biosynthesized AgNPs exhibited promising antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the antibacterial effects of the FI-AgNPs are owing to the interaction of AgNPs with the three-dimensional microbial structure of the cell walls of bacteria. The destruction of the bacterial cell wall may also be attributed to the release of ROS (reactive oxygen species) that can damage membrane protein and nucleic acid [52,53]. Bagherzadeh et al [54] compared the antibacterial effects of biosynthesized AgNPs prepared using saffron extract and market purchased AgNPs and showed that the extract of the saffron plant and purchased AgNPs did not show enough antibacterial effects but biosynthesized AgNPs exhibited promising antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
“…After incubation at 65 °C for 2 h, the dried powder of Ag-MMT-NPs was collected for further characterization [28]. In other previous similar investigations, the maximum volume used for synthesis of AgNPs has been 50 mL [18], but in our work the volume was increased to 2000 cc which resulted in synthesizing 2 g of silver nanoparticles. due to this information, we can claim that this method could be easily adopted for large-scale synthesis of NPs.…”
Section: Purification Of Silver Nanoparticlesmentioning
confidence: 95%
“…The absorption band at 3396.66/cm in the spectrum might be attributed to the stretching vibrations of secondary amines of N-H bond and bonded hydroxyl (-OH) groups of phenols and carboxylic acids [18]. Bonded hydroxyl (-OH) groups of carboxylic acids and phenols could produce absorption bands at 3396.66/cm (Fig.…”
Section: Ftir Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The scrutiny of the literature revealed some notable plant extract used for facile synthesis of AgNPs. For example, Nervalia zeylanica [31], Beutia monosperma [32], Leucaena leucocephala L. [18], Ipomoea digitata [33], Caesalpinia pulcherrima [34], Buddleja globosa [35], Sacha inchi [36], Peganum harmala [37], unripe fruit of Annona reticulata [38], Ziziphora tenuior [39], Caralluma fimbriata [40], root of Acanthospermum hispidum [41], Pistacia atlantica [42] and Rosa Chinensis L. [43] has been already reported.…”
Section: Introductionmentioning
confidence: 99%